Responsive peptide-based supramolecular hydrogels constructed by self-immolative chemistry. Issue 45 (14th November 2018) - Zheng, Debin; Gao, Zhengfeng; Xu, Tengyan; Liang, Chunhui; Shi, Yang; Wang, Ling; Yang, Zhimou
Abstract : Peptide-based supramolecular hydrogels that are stimuli-responsive under aqueous conditions have many potential biological applications, including drug delivery and sensing. Abstract : Peptide-based supramolecular hydrogels that are stimuli-responsive under aqueous conditions have many potential biological applications, including drug delivery and sensing. Herein, we reported a series of responsive peptide-based supramolecular hydrogels that respond to glutathione (GSH), nitric oxide (NO) and hydrogen sulfide (H2 S), which are biologically important signaling molecules. The responsive hydrogelators were designed by "self-immolative" chemistry and constructed by using self-immolative groups to modify short peptides. The self-immolative capping group could be removed in the presence of a corresponding trigger, thus causing gel–sol phase transitions. The potential of our responsive hydrogels for drug release was also demonstrated in this study. Our study offered several candidates of responsive hydrogels for sensing and drug delivery.